Attitudes About Perceived Park Safety Among Residents in Low-Income and High Minority Kansas City, Missouri, Neighborhoods. Issue 6 (July 2020) - Groshong, Lisa; Wilhelm Stanis, Sonja A.; Kaczynski, Andrew T.; Hipp, J. Aaron
Parks benefit communities by supporting the physical, mental, and social health of their residents. This is especially important in urban areas, where parks provide essential access to green space, and especially among low-income populations who may lack alternative venues for outdoor recreation. However, although urban parks may ostensibly be accessible, their use can be influenced by factors including perceptions and realities of safety. This qualitative study explored the issue of safety as it relates to park use and park-based physical activity from six focus groups with 41 total participants in urban Kansas City, Missouri. As a facilitator to safety, participants described social interactions and structural environment factors. Safety constraints emerged along five main themes: violence, concerning behavior, lack of maintenance, lack of lighting, and traffic/busy roads . This study adds to the literature establishing safety as a complex and multidimensional factor influencing park usage and physical activity.